It Is Impossible to Remain Silent - Radu, Ioanid (Indiana University Press, 2019)
Discover Elie Wiesel and Jorge Semprún in conversation. These two men, whose destinies were unparalleled, had probably crossed paths--without ever meeting--in the Nazi concentration camp Buchenwald in 1945. Both men offer riveting testimony and pay vibrant homage to the Jewish victims of the Holocaust.